Routledge handbook of agricultural biodiversity - Hunter, Danny; Guarino, Luigi; Spillane, Charlie; McKeown, Peter C. (Routledge handbooks., 2017)
"The world relies on very few crop and animal species for agriculture and to supply its food needs. In recent decades, there has been increased appreciation of the risk this implies for food security and quality, especially in times of environmental change. As a result, agricultural biodiversity has moved to the top of research and policy agendas. This Handbook presents a comprehensive overview of our current knowledge of agricultural biodiversity in a series of specially commissioned chapters. It draws on multiple disciplines including plant and animal genetics, ecology, crop and animal science, food studies and nutrition, as well as social science subjects which explore the socio-economic, cultural, institutional, legal and policy aspects of agricultural biodiversity. It focuses not only on the core requirements to deliver a sustainable agriculture and food supply, but also highlights the additional ecosystem services provided by a diverse and resilient agricultural landscape and farming practices. The book provides an indispensable reference textbook for a wide range of courses in agriculture, ecology, biodiversity conservation and environmental studies."--Provided by publisher